Forage biomass and water storage of cactus pear under different managements in semi-arid conditions - Lopes, Marcos Neves (2021)
Forage biomass production and water storage (WS) was evaluated in cactus pear cv. Gigante fertilized with combinations of nitrogen (10, 70, 100, 130, and 190 kg ha−1 yr−1 N) and phosphorus (10, 70, 100, 130, and 190 kg ha−1 yr−1 P2 O5 ) in annual (AH) and biennial (BH) harvest frequencies, in Quixadá and Tejuçuoca, Brazil. A randomized complete block design was used in a split-plot arrangement with four replications. In Quixadá, the maximum total forage biomass (TFB) recorded in the AH was 3,522.9 kg ha−1 yr−1 for the N/P2 O5 combination of 134.6/190.0 kg ha−1 yr−1, and in the BH, the maximum TFB of 1,583.2 kg ha−1 yr−1 was recorded for the N/P2 O5 combination of 114.6/136.8 kg ha−1 yr−1. In Tejuçuoca, the maximum TFB recorded in the AH was 9,783.0 kg ha−1 yr−1 for the N/P2 O5 combination of 137.7/190.0 kg ha−1 yr−1, and in the BH, the maximum TFB of 12,124.0 kg ha−1 yr−1 was recorded for the N/P2 O5 combination of 190.0/56.8 kg ha−1 yr−1. In Quixadá, the maximum WS recorded in the AH was 39.1 kg ha−1 mm−1 for the N/P2 O5 combination of 161.0/190.0 kg ha−1 yr−1, and in the BH, the maximum WS of 11.3 kg ha−1 mm−1 was recorded for the N/P2 O5 combination of 113.5/158.7 kg ha−1 yr−1. In Tejuçuoca, the maximum WS recorded in the AH was 196.1 kg ha−1 mm−1 for the N/P2 O5 combination of 190.0/190.0 kg ha−1 yr−1, and in the BH, the maximum WS of 265.5 kg ha−1 mm−1 was recorded for the N/P2 O5 combination of 190.0/10.0 kg ha−1 yr−1. To achieve the persistence and longevity of the cactus pear cv. Gigante, the management with BH and fertilization with the N/P2 O5 combination of 114.6/136.8 kg ha−1 yr−1 (in regions similar to Quixadá) and N/P2 O5 combination of 190.0/56.8 kg ha−1 yr−1 (in regions similar to Tejuçuoca) is recommended